Rhein-attenuates LPS-induced acute lung injury via targeting NFATc1/Trem2 axis - Xiang Li; Chuan Xiao; Jia Yuan; Xianjun Chen; Qing Li; Feng Shen (2023)
Evidence indicated that the early stage transition of macrophages' polarization stages yielded a superior prognosis for acute lung injury (ALI) or acute respiratory distress syndrome (ARDS). Rhein (cassic acid) is one major component of many traditional Chinese medicines, and has been reported to perform with strong anti-inflammation capabilities. However, the role rhein played and the mechanism via which it did so in LPS-induced ALI/ARDS remain unclear.ALI/ARDS was induced by LPS (3 mg/kg, i.n, st), accompanied by the applications of rhein (50 and 100 mg/kg, i.p, qd), and a vehicle or NFATc1 inhibitor (10 mg/kg, i.p, qd) in vivo. Mice were sacrificed 48 h after modeling. Lung injury parameters, epithelial cell apoptosis, macrophage polarization, and oxidative stress were examined. In vitro, conditioned medium from alveolar epithelial cells stimulated by LPS was used for culturing a RAW264.7 cell line, along with rhein administrations (5 and 25 μM). RNA sequencing, molecule docking, biotin pull-down, ChIP-qPCR, and dual luciferase assay were performed to clarify the mechanisms of rhein in this pathological process.Rhein significantly attenuated tissue inflammation and promoted macrophage M2 polarization transition in LPS-induced ALI/ARDS. In vitro, rhein alleviated the intracellular ROS level, the activation of P65, and thus the M1 polarization of macrophages. In terms of mechanism, rhein played its protective roles via targeting the NFATc1/Trem2 axis, whose function was significantly mitigated in both Trem2 and NFATc1 blocking experiments.Rhein promoted macrophage M2 polarization transition by targeting the NFATc1/Trem2 axis to regulate inflammation response and prognosis after ALI/ARDS, which shed more light on possibilities for the clinical treatments of this pathological process.